NEW OPPORTUNITIES FOR CORRECTION OF HYPERURICEMIA IN GOUT - Svetlana Evgenyevna Myasoedova; E A Kozhevnikova (Современная ревматология)
An open-labeled study of the efficiency and tolerability of the herbal preparation Urisan used for one month in 21 male gout patients has revealed that the agent has moderate antihyperurecemic activity, no adverse reactions, and excellent or good tolerability in the appraisal by physicians and patients.